(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2022)
Secondary structures, such as rafter stays, attached to the load-bearing element increase its stiffness, change its sketch and lead to a redistribution of internal forces. The influence of rafter stays on the bearing capacity of the frame elements was analyzed. A number of measures are considered to ensure the spatial stability of the linear elements of frame buildings, which lead to a decrease in the metal consumption of steel purlins. Based on the analysis of internal forces, the peculiarities of the working conditions of the beam were identified and described. It is proposed to increase material savings through detailed calculation. A comparison of design results is presented in software for calculating building models with portal frames